Characteristics of prescription of modern antacid drugs at acid-related diseases - A. S. Trukhmanov; I. V. Mayev; A. A. Samsonov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. The relevance of application of modern antacid agents in treatment of acid-related diseases is discussed.Original positions. Recent literature data testify high clinical efficacy of the modern combined antacids proved in series of multicenter clinical trials in patients with gastroesophageal reflux disease (GERD). It is revealed, that at non-erosive form of GERD monotherapy by Maalox is accompanied by high level (over 90%) of clinical remission achievement, improvement of scores of quality of life and safety.Conclusion. Antacid agents, along with antisecretory drugs (proton pump inhibitors), remain the important component of modern modes of treatment of basic acid-related diseases.